Mediation of Financial Literacy in Predicting Risk Tolerance on Muhammadiyah Organization Members in East Java - Mauliddah, Nurullaili; Danurwindo , Muhammad Alhakim; Ulum, Bahrul; Wibowo, Octavia Ika; Pravitasari, Galuh Nichayah (SENTRALISASI, 2023)
This study aims to predict risk tolerance and determine the role of financial literacy in members of the Muhammadiyah Organization in East Java through the mediation of financial literacy. This study took a sample of 107 respondents by using SEM-PLS analysis. The study results show that financial attitude, financial behaviour and income cannot predict risk tolerance. However, the effect of these independent variables on risk tolerance can be strengthened through the mediation of financial literacy. Thus, this study implies that members of the Muhammadiyah organization in East Java have a good level of risk tolerance supported by a good knowledge of financial concepts based on the measuring instrument in this research variable.